The activity of the Ministry of the Religious Denominations and Public Enlightenment in the Second Republic of Poland concerning natural conservation - Wolter, Edyta (Studia Ecologiae et Bioethicae, 2012)
The article covers the period between 1918 and 1939. The first part explains the normative acts which were the basis for nature conservation and cooperation between the Ministry of Religious Denominations and Public Enlightenment, the Polish Natural Science Museum in Warsaw, and the State Council for Nature Conservation. The second part presents the editorial activities of the State Council for Nature Conservation (the chairman of which was the Minister of Religious Denominations and Public Enlightenment) concerning nature conservation. The authors of the publication are Seweryn Dziubałtowski, Karol Domin, Andrzej Czudek, rev. Henryk Weryński, and Jan Sokołowski. The publication also includes the Act of March 10, 1934, on nature conservation, the provisions of this act being popular in Poland at that time due to the fact that the majority of the population were mainly peasants. 60% of Polish inhabitants lived in rural areas and worked on the land.